Barriers to adherence to iron chelation therapy among adolescent with transfusion dependent thalassemia - Mohamed, Rafaa; Abdul Rahman, Amir Hamzah; Masra, Farin; Abdul Latiff, Zarina (Frontiers in Pediatrics, 2022)
Thalassemia is the commonest genetic blood disorder in Malaysia which requires life-long blood transfusions. From a total of 7984 thalassemia patients in Malaysia, the adolescent age group accounts for the highest number of patients (2680 patients, 33.57%). In developed countries, the average rate of adherence to long-term treatment among children and adolescents is only 58%. Sub-optimal adherence to iron chelation therapy may impact the outcome and quality of life in patients with thalassemia. Thus, assessing adherence level and identification of risk factors for non-adherence is essential in optimising management. The objective of this study was to determine the association between mean serum ferritin level with self-reported level of adherence to iron chelation therapy amongst adolescents with transfusion dependent thalassemia (TDT) in two tertiary referral centres. The second objective was to determine the association between socio-demographic factors and patients' knowledge on thalassemia and iron chelation therapy with the level of adherence. This cross-sectional study was conducted between 1st March 2019 and 31st March 2020. Data was collected through face-to-face interview by a single interviewer during the thalassemia clinic follow up, with content validated questionnaires. The questionnaires comprised four sections which included socio-demographic data, medication adherence questionnaire, knowledge of disease and clinical characteristics of the participants. A total of 70 participants were recruited. Results showed that only 51.4% of participants had good adherence to iron chelation therapy. There was a significant association between monthly household income of the family with the level of adherence to iron chelation (p-value 0.006). There was also an association between the mean serum ferritin level with total Adherence Starts with Knowledge (ASK-12) score (p-value 0.001). However, there was no association between knowledge on thalassemia with the level of adherence. As our study showed that adherence remains to be an issue amongst adolescent thalassemia patients, overall management should include regular and objective assessments to address this problem so as to optimize patient outcome.